2021
DOI: 10.3390/ijms22062806
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Cyclin-Dependent Kinases: Types and Their Mechanism of Action

Abstract: Recent studies on cyclin-dependent kinase (CDK) inhibitors have revealed that small molecule drugs have become very attractive for the treatment of cancer and neurodegenerative disorders. Most CDK inhibitors have been developed to target the ATP binding pocket. However, CDK kinases possess a very similar catalytic domain and three-dimensional structure. These features make it difficult to achieve required selectivity. Therefore, inhibitors which bind outside the ATP binding site present a great interest in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 138 publications
(70 reference statements)
0
30
0
Order By: Relevance
“…These analyses highlighted that an inhibitor for CDK2 requires a bulkier ring to be attached to the main scaffold (the pyran ring in the present case) through a flexible chain of two to three atoms. Furthermore, it should be present at the periphery of the molecule to penetrate well inside the ATP binding site to establish lipophilic and mild polar interactions [ 69 ]. In addition, docking analyses indicated that H-bond donors or acceptors on the central scaffold could substantially enhance binding with the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…These analyses highlighted that an inhibitor for CDK2 requires a bulkier ring to be attached to the main scaffold (the pyran ring in the present case) through a flexible chain of two to three atoms. Furthermore, it should be present at the periphery of the molecule to penetrate well inside the ATP binding site to establish lipophilic and mild polar interactions [ 69 ]. In addition, docking analyses indicated that H-bond donors or acceptors on the central scaffold could substantially enhance binding with the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments in the field of small-molecule inhibitors of CDKs have led to several compounds with anticancer potencies both in vitro and in vivo and models of cancer. However, the specificity of the inhibitors, which inhibit close isoforms, is not fully achieved yet, especially for CDK5, which is involved in neurodegenerative diseases ( Łukasik et al, 2021 ). Other specific inhibitors have been developed with improved therapeutic effects, some of which are non-ATP competitive inhibitors that are selective and significantly less toxic than others like L803-mts as well as TDZD-8, VP0.7 ( Kaidanovich-Beilin et al, 2004 ; Kaidanovich-Beilin and Eldar-Finkelman, 2006 ).…”
Section: Post-translational Modifications In Alzheimer’s Diseasementioning
confidence: 99%
“…These drugs have using for the treatment of postmenopausal women with HR-positive, HER2-negative advanced, or metastatic breast cancer. The action mechanism is that inhibiting the phosphorylation of Rb protein in the G1 phase results in cell cycle arrest [127]. Palbociclib has a synergistic effect in combination therapy with either letrozole or fulvestrant [128].…”
Section: Cyclin-dependent Kinase (Cdk) Inhibitorsmentioning
confidence: 99%